Establishment of an Efficient Protoplast Regeneration and Transfection Protocol for Field Cress (Lepidium campestre) - Sandgrind, Sjur; Li, Xueyuan; Ivarson, Emelie; Ahlman, Annelie; Zhu, Li-Hua (Frontiers in Genome Editing, 2021)
Field cress (Lepidium campestre) is a potential oilseed crop that has been under domestication in recent decades. CRISPR/Cas9 is a powerful tool for rapid trait improvement and gene characterization and for generating transgene-free mutants using protoplast transfection system. However, protoplast regeneration remains challenging for many plant species. Here we report an efficient protoplast regeneration and transfection protocol for field cress. Important factors such as type of basal media, type/combination of plant growth regulators, and culture duration on different media were optimized. Among the basal media tested, Nitsch was the best for protoplast growth in MI and MII media. For cell wall formation during the early stage of protoplast growth, relatively high auxin concentrations (0.5 mg l-1 NAA and 2,4-D), without addition of cytokinin was preferred for maintaining protoplast viability. After cell wall formation, 1.1 mg l-1 TDZ combined with either 0.05 mg l-1 NAA or 2,4-D was found to efficiently promote protoplast growth. On solid shoot induction medium, 1.1 mg l-1 TDZ without any auxin resulted in over 80% shoot generation frequency. A longer culture duration in MI medium would inhibit protoplast growth, while a longer culture duration in MII medium significantly delayed shoot formation. Using this optimized protoplast regeneration protocol, we have established an efficient PEG-mediated transfection protocol using a vector harboring the GFP gene, with transfection efficiencies of 50-80%. This efficient protoplast protocol would facilitate further genetic improvement of field cress via genome editing, and be beneficial to development of protoplast regeneration protocols for related plant species.